GAMBARAN KLINIS GINGIVA PADA IBU HAMIL DI PUSKESMAS BAHU KECAMATAN MALALAYANG - Angwirawan, Lucyana S.; Ticoalu, Shane H. R.; Siagian, Krista V. (e-GiGi, 2015)
Abstract: Pregnancy is a very unique phase on every women marked with complex physiologic changes that can affect the healthiness of the oral cavity. The increased risk of mouth disease on pregnant women can be affected by the surge of estrogen and progesterone that marked by swelling and inflammation on the teeth. The General purpose of this research is to identify the clinical conception of the gingiva on pregnant women on Puskesmas Bahu in Malalayang residency. This research is tend to be observational descriptive with the cross-sectional approach. Population of this research is all the pregnant women that made a visit to Puskesmas Bahu in the period of January to February 2015 with 60 samples. The research on pregnant women can be divided with the scoring of gingiva clinical conception which is 0 for normal and 1 for abnormal on the color, size, contour, consistency and texture of the gingiva. The research result shows that the clinical picture of the gingiva on pregnant women are generally experience changes the texture of the gingiva (75%), followed by the gingiva consistency (73%), contour of the gingiva (58%), color of the gingiva (48%) and the size of the gingiva(43%). On the age category, the highest value of the percentage present on age 36 to 45 years old especially the changes on the texture of the gingiva (86%). On the category of age of the pregnancy, the highest value of the percentage present on the third trimester especially the changes of the the gingival consistency (86%).Keywords: clinical picture of gingiva, pregnant womenAbstrak: Kehamilan ialah masa yang sangat unik pada setiap wanita yang ditandai dengan perubahan fisiologis secara kompleks, sehingga dapat memengaruhi kesehatan rongga mulut. Peningkatan resiko terjadinya penyakit mulut pada wanita hamil dapat disebabkan oleh peningkatan hormon estrogen dan progesteron yang biasanya ditandai dengan pembengkakan dan peradangan pada gingiva. Tujuan dari penelitian ini ialah untuk mengetahui gambaran klinis gingiva pada ibu hamil di Puskesmas Bahu Kecamatan Malalayang. Penelitian ini bersifat deskriptif observasional dengan pendekatan cross sectional. Populasi dalam penelitian ini ialah seluruh ibu hamil yang dating berkunjung ke Puskesmas Bahu Kecamatan Malalayang pada bulan Januari – Februari tahun 2015 dengan jumlah sampel sebanyak 60 sampel. Penelitian pada ibu hamil dapat dibedakan dengan pembagian skor gambaran klinis gingiva yaitu normal sama dengan 0 dan tidak normal sama dengan 1 pada warna gingiva, besar gingiva, kontur gingiva, konsistensi gingiva dan tektur gingiva. Hasil dari penelitian ini menunjukkan bahwa gambaran klinis gingiva pada ibu hamil kebanyakkan mengalami perubahan pada tekstur gingiva (75%), diikuti berurut-turut konsistensi gingiva (73%), kontur gingiva (58%), warna gingiva (48%) dan besar gingiva (43%). Pada kategori umur presentase terbesar terdapat pada umur 36-45 tahun khususnya perubahan pada tekstur gingiva (86%). Pada kategori usia kehamilan presentase terbesar terdapat pada trimester ke – III khususnya perubahan pada konsistensi gingiva (86%).Kata kunci: gambaran klinis gingiva, ibu hamil